The Socioeconomic and Environmental Benefits of Bamboo Forest in Ethiopia: A Review - Rusha Begna Wakweya (Indonesian Journal of Social and Environmental Issues (IJSEI), 2023)
Bamboo plays a significant role in many socioeconomic aspects of life all over the world. Ethiopia, one of the African countries, is known for its high potential of bamboo forests. This paper aims to review the socioeconomic and environmental importance of bamboo forests in Ethiopia. The study used a critical review-based combination of searching for keywords such as bamboo, socioeconomic, environmental, benefit, Ethiopia, and inclusion and exclusion criteria to find relevant information. The results of this review indicated that bamboo has a substantial role in social, economic, and environmental purposes. However, the lack of awareness and consistent information about the socioeconomic benefits of bamboo forests in Ethiopia has been affecting its utilization for socioeconomic importance. Therefore, there is a need for awareness creation, such as training and development of bamboo markets and microenterprise industries in Ethiopia for socioeconomic and environmental benefits. The results of this paper can help farmers, extension workers, and policymakers by providing information on the conservation and proper utilization of bamboo forests for different socioeconomic and environmental purposes.